1994
DOI: 10.1210/endo.135.4.7925098
|View full text |Cite
|
Sign up to set email alerts
|

Catch-up growth after glucocorticoid excess: a mechanism intrinsic to the growth plate.

Abstract: In humans and other mammals, the release from growth-inhibiting conditions, such as glucocorticoid excess, leads to supranormal linear growth. The prevailing explanation for this catch-up growth involves a central nervous system mechanism that compares actual body size to an age-appropriate set-point and adjusts growth rate accordingly via a circulating factor. Although such a neuroendocrine "sizostat" was hypothesized more than 30 yr ago, its existence has never been confirmed experimentally. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(28 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Nonetheless, we did not observe any systemic effects of rapamycin. The tibial growth rate was most rapid in the first 4 weeks of the experiment, consistent with prior observations 26. The inhibitory effect of rapamycin on linear bone growth was most pronounced at the peak growth rate during the fourth week of infusion.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, we did not observe any systemic effects of rapamycin. The tibial growth rate was most rapid in the first 4 weeks of the experiment, consistent with prior observations 26. The inhibitory effect of rapamycin on linear bone growth was most pronounced at the peak growth rate during the fourth week of infusion.…”
Section: Discussionsupporting
confidence: 89%
“…5) in Ax 0 STZ rats, but it was elevated in a dose-dependent manner by corticosterone in both groups of STZ-injected animals. These results are consistent with previous reports (13,36), which suggested that the stimulatory effect of corticosterone on GH (7,17,40). Therefore, the failure of reduced IGF-I to cause a decrease in TEPW in the Ax nondiabetic rats (Table 1) is presumably due to the absence of corticosterone.…”
Section: Stzsupporting
confidence: 93%
“…Most glucocorticoid effects on endochondral bone growth appear to be due to direct regulation of chondrocytes, as opposed to generalized endocrine effects [11,12]. While effects of glucocorticoids on chondrocyte proliferation, differentiation and apoptosis as well as on vascular invasion of hypertrophic cartilage have been reported, the contributions of these effects to growth retardation and the molecular mechanisms involved are not completely understood [7,8,13].…”
Section: Introductionmentioning
confidence: 99%